DETERMINAN DISTRESS FINANSIAL BERDASARKAN STRUKTUR KEPEMILIKAN, LIKUIDITAS, DAN LEVERAGE - Pratama, Mochamad Ludvi; Retnani, Endang Dwi (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2022)
This research aimed to examine the effect of Ownership Structure, Liquidity, and Leverage on Distress finansial. The ownership structure was measured by Institutional Ownership. Meanwhile, Managerial Ownership, Liquidity, Current Ratio, and Leverage were measured by Debt to Asset Ratio. The research was quantitative. Moreover, the data collection technique used purposive sampling, in which the sample was based on the criteria given. In line with that, there were 70 samples from 10 Food and Beverage companies that were listed on Indonesia Stock Exchange (IDX) from 2014-up to 2020. The research result concluded that Institutional Ownership, as well as Managerial Ownership, had a negative effect on Distress finansial. It meant that the higher the Institutional and Managerial Ownership was, the lower the Distress finansial would be. On the other hand, liquidity did not affect Distress finansial. This meant that there were any other factors that would affect Distress finansial. In contrast, Leverage had a positive effect on Distress finansial. It happened as companies’ higher debt value could influence higher loans. Consequently, it affected financial burdens or companies’ Distress financial.